IMPLEMENTASI MODEL PBL BERBASIS PAPAN SPIN DALAM PEMBELAJARAN PENDIDIKAN PANCASILA PADA FASE C SDN REJOSARI 01 SEMARANG - Mulyaningsih; Patonah, Siti; Devega, Lidya Septia (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
The purpose of this study was to determine whether the use of norm spin board props has improved the learning outcomes of Pancasila Education VC students of SDN Rejosari 01 Semarang. This study used a two-cycle classroom action approach: implementation, planning, observation, and evaluation. This study involved 28 VC class students of SDN Rejosari 01, consisting of 12 boys and 16 girls. The data collection methods are formative tests and non-formative tests, and the research tools are formative test sheets and observation sheets. The data were analyzed with two approaches: quantitative analysis determines the cognitive learning outcomes of individuals; and qualitative analysis evaluates student activities and teacher proficiency. The independent variable of this study is the learning of Pancasila Education with the help of norm spin board props, and the dependent variable is the improvement of learning outcomes of VC class students of SDN Rejosari 01 about the norm material in my life. The implementation of actions is carried out 2 cycles. Learning outcomes from cycle I, 17 students who have not finished with a completeness percentage score of 54.28% and cycle II where 25 students complete a completeness percentage score of 80.35%. Cycle I student activities, 9 students incomplete scores percentage 25% category less (K) and cycle II 25 students percentage value 80.35% good category (B). Teacher skills cycle I value 59 categories less (K) and cycle II value 86 categories good (B).